2015
DOI: 10.1016/j.psychres.2015.09.010
|View full text |Cite
|
Sign up to set email alerts
|

‘No man is an island’. Testing the specific role of social isolation in formal thought disorder

Abstract: Recent work has focused on the role of the environment in psychosis with emerging evidence that specific psychotic experiences are associated with specific types of adversity. One risk factor that has been often associated with psychosis is social isolation, with studies identifying isolation as an important feature of prodromal psychosis and others reporting that social networks of psychotic patients are smaller and less dense than those of healthy individuals. In the present study, we tested a prediction tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 113 publications
(138 reference statements)
2
15
0
Order By: Relevance
“…The relationship between social isolation and TD was more interesting. First, it replicates previous findings from our own and other research groups (Badcock et al, 2015;de Sousa et al, 2015), and second, in contrast to what has previously been suggested (Freeman et al, 2002;Hoffman, 2007) neither hallucinations nor delusions or suspiciousness correlated with social isolation (it is unclear why unusual beliefs did not correlate with social isolation. One possibility is social isolation may be specifically associated with strength of conviction and other variable rather than unusual beliefs).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The relationship between social isolation and TD was more interesting. First, it replicates previous findings from our own and other research groups (Badcock et al, 2015;de Sousa et al, 2015), and second, in contrast to what has previously been suggested (Freeman et al, 2002;Hoffman, 2007) neither hallucinations nor delusions or suspiciousness correlated with social isolation (it is unclear why unusual beliefs did not correlate with social isolation. One possibility is social isolation may be specifically associated with strength of conviction and other variable rather than unusual beliefs).…”
Section: Discussionsupporting
confidence: 88%
“…We have previously reported a significant and sizable relationship between TD, measured during a purposely-designed set of interviews, and self-reported social isolation (de Sousa et al, 2015). Importantly, this relationship remained significant…”
Section: Social Isolation and Tdmentioning
confidence: 83%
“…The descriptive statistics for the demographic and clinical variables can be found elsewhere (De Sousa et al, 2015) and in Table 1. Briefly, the groups did not differ significantly on variables such as gender, age, or ethnicity.…”
Section: Resultsmentioning
confidence: 99%
“…Second, references from pertinent qualitative review articles [1,44] were examined for additional references not detected through the initial search. Third, forward searches of articles directly examining the link between FTD and social functioning [7,15,[45][46][47][48][49] were conducted to find additional articles.…”
Section: Literature Searchmentioning
confidence: 99%
“…Despite longstanding observation, empirical evidence of the relationship between FTD and social functioning deficits in schizophrenia is unclear. Across studies, the magnitude of associations has varied from negligible [13,14] to large [15]. To date, no meta-analysis has synthesized findings to clarify the relationship between FTD and social functioning.…”
Section: Introductionmentioning
confidence: 99%